(untitled) (Fiep Bulletin - online, 2013)
This article aims to discuss the presence of girls in an exclusively male stronghold before the skateboard. The objectives: (a) discuss the presence of the tribe of girls who chose to attend and skate boards in a scenario dominated by boys, (b) discuss performance from their performance, and (c) highlight the symbolic elements that emerge from the speeches served in the tribe of girls skaters. The study examines qualitative nature of the speeches of the girls through the Analysis of Speech (AD), of Orlandi (2001) projective technique associated with the Association of Ideas. The technique aims to explore the mental associations, helping the researcher to penetrate the subjectivity of the subject and the symbolic capture him. 10 girls were interviewed and analyzed blogs specific to the subject. It was concluded that the girls skaters, to choose their sports away from the dreams of many mothers, adhere to slide into the boards by skateboard ramps and streets of the city. This attraction is similar to an adventure in which the practitioners to print their actions challenging the real sense, including overcoming all barriers that society imposes on them. Blessed by Artemis are endowed with great strength: the independence, autonomy and desire to achieve things.